Brazilian medical oncologists: current and future perspectives for 2020 - Portich, Júlia Plentz; Giacomazzi, Juliana; Morelle, Alessandra Menezes; Rosa, Daniela Dornelles; Rossari, José Roberto Freitas; de Azambuja, Evandro (Brazilian Journal of Oncology, 2017)
Objective: In the USA there will be a shortage of medical oncologists by 2020. In Europe, a recent study showed that almost all analyzed countries will reach the estimated need. However, no data on this subject is available for Brazil, a developing country with a high cancer incidence. The aim of this study was to predict the Brazilian scenario for 2020. The number of practicing medical oncologists was obtained through Federal Council of Medicine in August 2014.Methods: Data on cancer incidence (excluding non-melanoma skin cancer) since 2008 were obtained from Brazilian National Cancer Institute (INCA).Results: Cancer incidence estimates for year 2020 were analyzed assuming a stable increase between 2014 and the subsequent years. Ratios of new cancer cases versus number of medical oncologists were calculated for 2014 and for 2020 per each Brazilian region. Based on the variation ratio per year, the Brazilian cancer incidence in 2020 is estimated to be 393,75/100,000 compared with 289,44/100,000 in 2014. The number of medical oncologists in Brazil will increase by 2020 in comparison to 2014, especially due to the growth of training vacancies. There will still be a heterogeneous distribution of medical oncologists through the different Brazilian regions and also a high number of patients per MO.Conclusion: The more critic region to oncology care seems to be the Midwest. This survey shows the need of a monitoring and planning program in oncology assistance in all Brazilian regions.
Keywords: Neoplasms/epidemiology; Physicians; Medical hole; Brazil